Peningkatan Pengetahuan dan Sikap Pencegahan Diare Melalui Edukasi dengan Menggunakan Media Audio Visual pada Siswa Sekolah Dasar - Galuh Ambariandi; Sumardino Sumardino; Tri Sunaryo (Poltekkes Kemenkes Surakarta, 2024)
Background: Diarrhea remains one of the leading causes of death in children, making prevention and control efforts crucial. Health education, using media such as leaflets and audio-visual tools, plays a vital role in raising awareness. This activity aims to implement a school-based community service programme and evaluate the improvement in knowledge and attitudes towards diarrhoea prevention among fifth-grade students at SDN Temboro 1 after audiovisual-based health education. Methods: This school-based PkM programme presented audiovisual modules on diarrhoea prevention to 36 fifth-grade students and conducted pre- and post-tests to monitor their learning outcomes. Knowledge was measured using a structured questionnaire (multiple choice/true-false), and attitudes were measured using a 4-point Likert scale; both were administered immediately before and after the session. Results: Pre- and post-monitoring showed improvement in both approaches; the audiovisual group recorded an average knowledge score of 70.89 and an attitude score of 66.33 after the session. These findings confirm that audiovisual education is more effective in optimising understanding and attitudes towards diarrhoea prevention in the context of school-based PkM. Conclusion: Audio-visual health education proves to be an effective method in enhancing both knowledge and attitudes toward diarrhea prevention in elementary school students.